Quantitative evaluation of prospective motion correction in healthy subjects at 7T MRI. Issue 2 (31st August 2021) - Sciarra, Alessandro; Mattern, Hendrik; Yakupov, Renat; Chatterjee, Soumick; Stucht, Daniel; Oeltze‐Jafra, Steffen; Godenschweger, Frank; Speck, Oliver
Abstract : Purpose: Quantitative assessment of prospective motion correction (PMC) capability at 7T MRI for compliant healthy subjects to improve high‐resolution images in the absence of intentional motion. Methods: Twenty‐one healthy subjects were imaged at 7 T. They were asked not to move, to consider only unintentional motion. An in‐bore optical tracking system was used to monitor head motion and consequently update the imaging volume. For all subjects, high‐resolution T1 (3D‐MPRAGE), T2 (2D turbo spin echo), proton density (2D turbo spin echo), and T 2 ∗ (2D gradient echo) weighted images were acquired with and without PMC. The images were evaluated through subjective and objective analysis. Results: Subjective evaluation overall has shown a statistically significant improvement (5.5%) in terms of image quality with PMC ON. In a separate evaluation of every contrast, three of the four contrasts (T1, T2, and proton density) have shown a statistically significant improvement (9.62%, 9.85%, and 9.26%), whereas the fourth one ( T 2 ∗ ) has shown improvement, although not statistically significant. In the evaluation with objective metrics, average edge strength has shown an overall improvement of 6% with PMC ON, which was statistically significant; and gradient entropy has shown an overall improvement of 2%, which did not reach statistical significance. Conclusion: Based on subjective assessment, PMC improved image quality in high‐resolution images of healthy compliant subjects in the absence of intentional motion for all contrasts except T 2 ∗, in which no significant differences were observed. Quantitative metrics showed an overall trend for an improvement with PMC, but not all differences were significant.